2017
DOI: 10.17925/enr.2017.12.02.92
|View full text |Cite
|
Sign up to set email alerts
|

Parkinson’s Disease Psychosis – Patterns of Care and Treatment in the EU-5 from Neurologists’ Perspective

Abstract: Over half of patients with Parkinson’s disease (PD) develop symptoms of psychosis during the course of their disease. Existing guidelines include recommendations for managing symptoms of psychosis in patients with PD. However, the extent to which such recommendations translate to clinical practice in major European nations is unclear. The current study describes trends in the clinical management of patients diagnosed with PD psychosis (PDP) based on survey responses and patient chart reviews from 437 neurologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
(28 reference statements)
1
3
0
Order By: Relevance
“…Data on PDP treatment patterns among neurologists in the EU-5 are also limited and are presented in a separate report. 33 In the current study, the estimated prevalence rates for PDP among patients with PD in the EU-5 nations are in line with those reported in previous studies.…”
Section: Disruptiveness and Comorbidity Ratessupporting
confidence: 91%
See 1 more Smart Citation
“…Data on PDP treatment patterns among neurologists in the EU-5 are also limited and are presented in a separate report. 33 In the current study, the estimated prevalence rates for PDP among patients with PD in the EU-5 nations are in line with those reported in previous studies.…”
Section: Disruptiveness and Comorbidity Ratessupporting
confidence: 91%
“…A report of survey data related to treatment patterns for patients with PDP in the EU-5 is presented in a separate report. 33 …”
Section: Resultsmentioning
confidence: 99%
“…When pharmacotherapy for PD psychosis is indicated, the most recent Movement Disorders Society Evidence‐Based Medicine review identified clozapine and pimavanserin as efficacious and “clinically useful.” Quetiapine was deemed “possibly useful” due to insufficient clinical trial evidence 3 . Because pimavanserin is newly available in the United States and clozapine requires specialized monitoring, quetiapine remains a frequently used first‐line agent for the treatment of PD psychosis 4–6 …”
mentioning
confidence: 99%
“…3 Because pimavanserin is newly available in the United States and clozapine requires specialized monitoring, quetiapine remains a frequently used first-line agent for the treatment of PD psychosis. [4][5][6] Approved by the US Food and Drug Administration (FDA) in 2016, pimavanserin is the only medication specifically indicated for the treatment of PD psychosis in the United States. Pimavanserin is distinct from other antipsychotics because its mechanism of action is via serotonin (5-HT) 2A receptor activity and avoids effects on dopamine receptors, which can worsen parkinsonism.…”
mentioning
confidence: 99%